Types and reason of code mixing found in dedy corbuzier conversation in the podcasts - Harman, Stefanus; sulatra, I komang (Institut Pariwisata dan Bisnis Internasional, 2022)
The study concerns the code mixing found in Deddy Corbuzier conversation in the podcasts.. The objectives of this research are to classify the types and to analyze the reasons of code mixing found in Deddy Corbuzier conversation in the podcasts. The writer analyzed the types of code mixing based on theory by Hoffman (1983: 75) and theory by Hoffman (1991) was used to analyze the reasons In this research, descriptive qualitative is used as the method of the analysis. The data were taken from one video of Chef Juna-Guy? Jahanam? Silahkan. This researcher shows that all types of code-mixing, such as intra sentential mixing, intra lexical code mixing, and involving a change of pronunciation were found in Deddy Corbuzier conversation in the podcasts. Meanwhile, the reasons for code mixing found in the podcasts were talking about a particular topic, expressing feelings about something, and the last, the most dominant one was intention of clarifying the speech for the interlocutor. Some of the reasons were not found data such as, quoting someone words, interjection (inserting sentences filler or sentences connector), repetition used for clarification, expressing group identity.